PELAKSANAAN PENDIDIKAN KARAKTER DI MADRASAH ALIYAH NEGERI 2 PALEMBANG - Sukirman Sukirman; Akmal Hawi; Alimron Alimron (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2017)
Moral degeneration has become a common phenomenon that plagues mankind in various parts of the world today, including in Indonesia. Various moral cases have occurred and adorned mass media almost all the time, ranging from cases of corruption, acts of violence, sexual harassment, pornography, prostitution, drug abuse, even murder. Since 2010 the Center for Curriculum and Bookkeeping has initiated a pioneering program of character education implementation in several districts / cities in all provinces in Indonesia.This study uses a combination of quantitative and qualitative approaches. The data were collected using interviews and questionnaires. Data analysis is done descriptively in order to explain / describe the implementation of character education and the factors that become obstacles of its implementation.In this research can be concluded that character education in MAN 2 Palembang has not been implemented maximally. Some things that have not been implemented related to the implementation of character education are: not all contextual learning strategies used, not all teachers use contextual learning strategies, there has been no specific effort to revitalize the activities of co-curricular and extra curricular, related to the integration of teachers in learning, there are still 33.33 % of teachers are doing poorly (20.8% are poor in learning planning, 25% on learning implementation aspects, and 4.2% on learning assessment aspects). Many factors constraints and support the implementation of character education in MAN 2 Palembang. The obstacles faced by the madrasah include: difficulty in carrying out routine activities, difficulties in performing spontaneous activities, and difficulties in conducting conditioning activities. While the constraints factor from the teacher side is the difficulty of integrating character education in the learning process, which include: difficulties linking character education with materials, methods, strategies, and learning media, difficulty determining the value of character to be achieved, difficulty measuring the attainment of character education in participants students, too many students per class, not all teachers and employees can be role models, the number of things that affect the character, as well as the many aspects of character that must be developed. While the factors supporting the implementation of character education in MAN 2 Palembang include: support of all madrasah residents, family environment, madrasah infrastructure facilities, budget, student association, and student motivation.